Optic Disc Pit Maculopathy: A Review. Issue 3 (May 2019) - Kalogeropoulos, Dimitrios; Ch'ng, Soon Wai; Lee, Rynn; Elaraoud, Ibrahim; Purohit, Maninee; Felicida, Vinaya; Mathew, Magie; Ajith-Kumar, Naduviledeth; Sharma, Ash; Mitra, Arijit
Abstract : Abstract: Optic disc pit (ODP) is a rare congenital anomaly of the optic disc that can be associated with maculopathy leading to progressive visual deterioration. The vast majority of cases are sporadic and no obvious factors have been correlated with the development of maculopathy. Optic disc pit maculopathy is defined by the concentration of intraretinal and subretinal fluid at the area of macula. Despite the advances in the imaging of the fundus, the origin of the fluid remains unknown and the exact pathogenesis of the maculopathy is not fully understood. Although some cases have been reported to resolve spontaneously, most cases require surgical intervention in order to treat ODP maculopathy and prevent loss of vision. Currently, there is no definite treatment for these patients and several surgical methods have been described, including pars plana vitrectomy (PPV) (combined with various techniques, such as inner retinal fenestration, autologous fibrin, and glial tissue removal), laser photocoagulation, intravitreal gas injection, and macular buckling. Overall, PPV remains the main form of surgical repair of ODP maculopathy. Although our understanding of the background and the pathophysiology of the disease has significantly improved, more studies are required in order to define the optimal treatment. This review summarizes the potential pathogenesis, as well as the diagnostic and therapeutic approach of ODP maculopathy.